Association Between Daily Worry, Pathological Worry, and Fear of Progression in Patients With Cancer - Dinkel, Andreas; Marten-Mittag, Birgitt; Kremsreiter, Katrin (Frontiers in Psychology, 2021)
Background: Fear of progression (FoP), or fear of cancer recurrence (FCR), is characterized by worries or concerns about negative illness-related future events. Actually, to worry is a common cognitive process which, in its non-pathological form, belongs to daily life. However, worry can also become pathological appearing as a symptom of mental disorders. This study aimed at investigating the associations among daily worry, pathological worry, and fear of progression in patients with cancer. Methods: This is a cross-sectional study that includes 328 hospitalized patients with cancer. Patients filled out the Fear of Progression Questionnaire (FoP-Q), the Worry Domains Questionnaire (WDQ) for the assessment of daily worry, and the Penn State Worry Questionnaire (PSWQ) for the assessment of pathological worry. Depressive, anxiety and somatic symptoms were measured with modules of the Patient Health Questionnaire (PHQ-2, GAD-2, PHQ-15). Furthermore, a structured clinical interview was applied for the assessment of anxiety disorders. Hierarchical multiple linear regression was used to identify factors independently associated with FoP. Results: Mean age of the participants was M = 58.5 years (SD = 12.8), 64.6 % were men. FoP and worry were significantly intercorrelated (r = .58 to r = .78). Level of FoP was most strongly associated with daily worry (beta = .514, p < .001), followed by pathological worry (beta = .221, p < 001). Further significant determinants were younger age, depressive and anxiety symptoms. Clinical variables were not independently associated with FoP. The final model explained 74 % of the variance. Discussion: Fear of progression is strongy associated with daily worry and pathological worry. These results bring up the question whether FoP is an expression of a general tendency to worry. Whether a general tendency to worry, in fact, represents an independent vulnerability factor for experiencing FCR/FoP needs to be investigated in a longitudinal research design.